Utilization of petrographic analysis for determination of petroleum coke mixtures - Toprak, Selami; Sutcu, Emine Cicioglu; Gulen, Fatma Jale (Tubitak Scientific & Technological Research Council Turkey, 2014)
This study was carried out on mostly imported, processed petrocokes, which are also commercially known as petcoke or petroleum coke. Petrocoke is imported in great amounts and is occasionally consumed domestically without conscientious thought. It is not a well-known material, though there is an idea of its genesis. The samples, their analysis, and their images are essential to be kept in mind for further investigations, since it is not an environmentally friendly material. Petrographic and chemical analyses were conducted on all samples. Trace element and FT-IR analyses were made on a few representative samples. It is possible to distinguish petrocokes from coal samples by means of coal petrography. Even mixtures of the petrocokes with coals can be detected very well. Some trace elements such as V, U, and Ni have much higher contents in petrocokes. They may cause environmental impacts.
Keywords: Petrocoke; petrocoke-coal blend; petrocoke determination; petrocoke petrographic analysis; FT-IR analysis; trace elements in petrocokes; petroleum coke; Geology